New Allogeneic Hematopoietic Stem Cell Transplantation Method: Hematopoietic Stem Cell Transplantation Plus Thymus Transplantation for Intractable Diseases - Naoki Hosaka (Clinical and Developmental Immunology)
Although allogeneic hematopoietic stem cell transplantation (allo-HSCT) has become a valuable strategy for some intractable diseases, a number of problems remain to be resolved. We have developed a new HSCT method, HSCT + thymus transplantation (TT) from the same donor, which induces elevated T cell function with mild graft-versus-host disease (GVHD) in comparison to conventional HSCT alone and HSCT + donor lymphocyte infusion (HSCT + DLI). This new method is effective in the treatment of several intractable diseases and conditions, such as autoimmune diseases in aging, advanced malignant tumors, exposure to supralethal irradiation, multiple organ transplantation from different donors, and type 2 diabetes mellitus, for which conventional methods are ineffective. Our findings suggest that allo-HSCT + TT is preferable to conventional allo-HSCT alone or allo-HSCT + DLI. This method may become a valuable next-generation HSCT technique.